Clinicoetiological profile of pyrexia of unknown origin in children 1-12 years of age in a tertiary care centre - Surong, Nafisha; Joseph, Dibin (International Journal of Contemporary Pediatrics, 2023)
Background: A primary concern of the paediatricians in evaluating a child with PUO is the limited use of investigations that are case-specific especially in developing countries such as India where availability and affordability are the limiting factors. Hence, this study was conducted to evaluate the various etiological factors and the clinical profile of children presenting with PUO in this region. Methods: A hospital based cross sectional study was conducted among 200 children presenting with fever i.e., temperature >100.9⁰F/38.3 ⁰C of more than one week duration, with no clear diagnosis after initial investigations Results: A total of 193 children were included in the study with a mean age of 6.2±1.8 years. Most (62.5%) of the participants had infectious etiology, followed by collagen vascular disorders (10 %) and malignancies (9.5%). Among the participants, 10% remain undiagnosed. Among infectious causes, the most common was respiratory tract infections (17.5%), followed by scrub typhus (13.5%) and urinary tract infections (10%). Conclusions: Our study was conducted to outline the clinic-etiological profile of pediatric patients with PUO in our region. After proper investigations, a diagnosis could be reached in most patients. The commonest aetiology was infectious, followed by collagen vascular disorders and malignancies. Further studies with a larger sample size are suggested.